IMPLEMENTASI KEBIJAKAN PROGRAM KELUARGA HARAPAN (PKH) PEMERINTAH KELURAHAN BUKIT WOLIO INDAH KECAMATAN WOLIO KOTA BAUBAU - La Ode Dwiyan Pramono Darmin; Jasir B. Jasir B.; Ilham Ilham (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
This research describes the implementation of family hope program policy, especially in Bukit Wolio Indah Village, Baubau City. In its implementation, the facilitators play a crucial role in carrying out this program. This research uses qualitative methods. Data were collected through interviews, observations, and documentation. The data were analyzed by organizing the substantive data, reducing it without changing the substantive information, and then presenting the data. The data were presented while still taking into account the freshness of the data, starting from credibility, transferability, dependability to conformability. The research found that: firstly, the implementation of the Family Hope Program (PKH) policy has been organized and does not result in various policy interpretations, but this policy has not been successfully applied because many of the PKH beneficiaries are still not independent, with a total of 300 PKH beneficiary families. The policy was organized by involving the local government agencies, the Social Department and the Village Government, supported by the district facilitators. Secondly, the facilitators also serve as motivators, besides serving as facilitators and bridging the gap in validation data between the central government and the social service agency, which was often a problem in determining the target group of recipients. However, these roles are still not able to make the PKH beneficiaries independent.